PENGARUH TEMAN SEBAYA TERHADAP PSIKOSOSIAL REMAJA - Husna, Nurul; Ruaidah, Ruaidah; Zulhendri, Zulhendri (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of writing this article is to provide a conceptual description of the influence of peers (peer groups) on adolescent psychosocial. The results of the discussion show that Peer groups are successful peer groups where children can interact. Peer groups are very influential on adolescent self-image. Adolescents become closer to their peers, because they think that their peers can understand their desires so they want to spend time with their friends. Peer group qualities consist of positive friendship qualities (such as feelings of security, friendship, support) and negative friendship qualities (such as conflict, dominance, hostility). Therefore, in association, both individuals and groups must be able to learn to behave in order to lead to a better life. Peer groups (peer groups) need discipline so that in carrying out group activities they gain recognition from the community. Therefore, the peer group is very important to note because it has a fairly important role for the development of adolescents.